Pengaruh E-Commerce, Digital Payment, Self-Efficacy dan Sistem Informasi Akuntansi dalam Pengambilan Keputusan Berwirausaha (Studi Kasus pada Mahasiswa Akuntansi Universitas Muhammadiyah Surakarta Angkatan 2020) - Fahmi, Agmi Rahayu; Fauzan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this study was to analyze the effect of e-commerce, digital payment, self-efficacy and accounting information systems on entrepreneurial decision making (case study on Accounting students of Universitas Muhammadiyah Surakarta class of 2020). This type of research is quantitative. The population used in this study is accounting students of Universitas Muhammadiyah Surakarta class of 2020 with a total of 492 students. The data was obtained from the official website of Universitas Muhammadiyah Surakarta. The sample collection technique in this study used nonprobability sampling techniques. This study uses primary data. The data collection technique in this study used questionnaire data. Data analysis techniques used are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, hypothesis testing, t test, f test, and determination coefficient test (R2). The results of this study are that E-Commerce has no effect on Decision Making for Entrepreneurship. Digital Payment has no effect on Decision Making for Entrepreneurship. Self-Efficacy has a positive effect on Decision Making for Entrepreneurship. Accounting Information System has no effect on Decision Making for Entrepreneurship.